1975
DOI: 10.1159/000468179
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Bromazepam (Ro 5-3350, Lexotan®) and Diazepam (Valium®) in Anxiety Neurosis

Abstract: The new benzodiazepine bromazepam (Ro 5-3350, Lexotan®) was compared with diazepam in a double-blind, crossover trial on 30 patients with prolonged anxiety symptoms. Each drug was given for 3 weeks in a dose of 5 mg t.d.s. Bromazepam proved to be statistically significantly superior to diazepam when evaluated through patients’ preferences. Fourteen patients preferred bromazepam to diazepam and four the opposite. Three cases were tied. Nine patients had to be withdrawn from the evaluation, which may create bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Like all benzodiazepines, bromazepam proved to possess muscle relaxing activity, antineurotic and sedative effects [3][4][5]. The most characteristic effect of bromaze- pam is its anxiolytic power [6], which in clinical trials has been shown to be at least equal to [7,8] or superior than [9][10][11] that of diazepam and of lorazepam [12]. Bromazepam has also been shown to be effective as oral premedication in gynecological surgery [13,14] and to possess a good gastroprotective potential against stress-induced gastric ulceration, mediated by the inhibition of gastric secretion [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Like all benzodiazepines, bromazepam proved to possess muscle relaxing activity, antineurotic and sedative effects [3][4][5]. The most characteristic effect of bromaze- pam is its anxiolytic power [6], which in clinical trials has been shown to be at least equal to [7,8] or superior than [9][10][11] that of diazepam and of lorazepam [12]. Bromazepam has also been shown to be effective as oral premedication in gynecological surgery [13,14] and to possess a good gastroprotective potential against stress-induced gastric ulceration, mediated by the inhibition of gastric secretion [15][16][17].…”
Section: Introductionmentioning
confidence: 99%